The impact of administrative creativity in managing change organization in institutions" An applied study on The Ministry of Finance, Economy and Investment, Khartoum State - Yousif, Mohammed Ahamed Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to know the impact of administrative creativity in managing organizational change in institutions by applying to the Ministry of Finance, Economy and Investment in the state of Khartoum, Her problem was summarized in a number of questions, including: To what extent does administrative creativity affect the management of organizational change in the Ministry of Finance, Economy and Investment in the state of Khartoum?, To what extent does the Ministry of Finance, Economy and Investment use administrative creativity in managing its internal conflicts?, The study used the descriptive analytical method, the case study method, and the SPSS program, The study reached several results, the most important of which are the existence of a statistically significant relationship between administrative creativity and the management of organizational change in the Ministry of Finance, Economy and Investment in the state of Khartoum, the existence of a statistically significant relationship between administrative creativity and internal conflict management in the Ministry of Finance, Economy and Investment in Khartoum state, Finally, the study recommended the following: The senior management of the Ministry of Finance should create the appropriate regulatory environment that encourages the application of the administrative creativity method among all its administrative levels, The senior management in the Ministry of Finance must activate the participation of all its employees in the process of organizational change and transform resistance to change into strengths that help effect change effectively.